The nuclear mRNA export receptor Mex67-Mtr2 of Trypanosoma brucei contains a unique and essential zinc finger motif - Dostalova, Anna; Käser, Sandro; Cristodero, Marina; Schimanski, Bernd (Molecular microbiology, 2013)
Trypanosoma brucei is the causative agent of Human African Trypanosomiasis. Trypanosomes are early diverged protozoan parasites and show significant differences in their gene expression compared with higher eukaryotes. Due to a lack of individual gene promoters, large polycistronic transcripts are produced and individual mRNAs mature by trans-splicing and polyadenylation. In the absence of transcriptional control, regulation of gene expression occurs post-transcriptionally mainly by control of transcript stability and translation. Regulation of mRNA export from the nucleus to the cytoplasm might be an additional post-transcriptional event involved in gene regulation. However, our knowledge about mRNA export in trypanosomes is very limited. Although export factors of higher eukaryotes are reported to be conserved, only a few orthologues can be readily identified in the genome of T. brucei. Hence, biochemical approaches are needed to identify the export machinery of trypanosomes. Here, we report the functional characterization of the essential mRNA export factor TbMex67. TbMex67 contains a unique and essential N-terminal zinc finger motif. Furthermore, we could identify two interacting export factors namely TbMtr2 and the karyopherin TbIMP1. Our data show that the general heterodimeric export receptor Mex67-Mtr2 is conserved throughout the eukaryotic kingdom albeit exhibiting parasite-specific features.
Keywords: proteiny vázající RNA; RNA-Binding Proteins; Zinc Fingers; aktivní transport - buněčné jádro; nukleocytoplazmatické transportní proteiny; messenger RNA; RNA, Messenger; zinkové prsty; Nucleocytoplasmic Transport Proteins; Active Transport, Cell Nucleus; jaderné proteiny; Trypanosoma brucei brucei; Nuclear Proteins